Gender differences in the ability to sustain large fractions of anaerobic velocity in endurance runs - Sucec, A. A.; Burks, J.; Buffington, S.; Trone, D. (Medicine & Science in Sports & Exercise, 1998)
Endurance runners (M = 20; F = 20) ran 400 m to establish a measure of maximal anaerobic velocity. In random order they also performed all-out runs over 800 m, 1,500 m, 3 km, 5 km, and 10 km on separate days. The mean velocity for 10 km for females was 74.6% and for males 68.4% of the maximal anaerobic velocity, a statistically significant difference. It was then found that the female Ss had covered a significantly greater total mileage than the male Ss in training over the previous 12 months. Thus, it is possible the difference in percentage maximal anaerobic velocity could be related to total miles trained. Other reasons for the difference were postulated as being better beta oxidation, ability to sustain higher fractions of VO2max, and psychological differences. Implication. Female endurance runners are able to sustain a greater proportion of maximal anaerobic velocity than males over the same differences.